Drug Interactions in Diabetic Ulcer Patients in an Indonesian Private Hospital - Finny Alifiyatur Roosyidah; Rika Yulia; Fauna Herawati; Heru Wijono (Faculty of Medicine, Universitas Padjadjaran, 2023)
Diabetic ulcers can progress into tissue death, or gangrene, which create a risk for amputation. Measures for preventing other complications and accelerating wound healing in diabetic ulcers include blood sugar level control, diet adjustment, wound care, antidiabetic drug administration, and comorbid therapy. This leads to the use of various drugs that can potentially trigger drug interactions. This study aimed to identify possible drug interactions in the therapeutic management of diabetic ulcer patients treated in Husada Utama Hospital Surabaya, Indonesia, from January 2020–June 2022. This was a descriptive observational study using retrospective data from medical records. Results showed that 103 types of drugs were administered to 48 research samples with 41 of them experienced drug interactions (n=263 cases). Based on the severity of drug interactions, 31 cases were categorized as major cases (11.79%), with drug-class antibiotic-antiemetic interactions as the most frequent interactions. This study proves that it is essential for doctors and pharmacists.